Knowledge of cervical cancer risk factors among students at the Jan Kochanowski University in Kielce - Piotr Lewitowicz; Agata Horecka-Lewitowicz; Olga Adamczyk-Gruszka (Studia Medyczne, 2013)
Introduction : Cervical cancer is the third most common malignant tumour in women. As far as we know today, the main cause of cervical cancer is human papilloma virus (HPV) infection with high grade oncogenic HPV genotypes, as well as co-occurrence of other factors predisposing women to cervical cancer. According to the WHO, the factors include smoking, multiple sexual partners, low socioeconomic status, herpes simplex virus (HSV) co-infection, human immunodeficiency virus infection, and antioxidant and vitamin insufficiency in the diet. Aim of the research : To assess the knowledge of cervical cancer among young women. Material and methods: The survey was carried out in 2010–2012 in a group of 149 female students at the age of 20 ±1 at the Jan Kochanowski Memorial University, Kielce prior to gynaecology, pathology and oncology classes. The questionnaire survey included closed multiple choice questions. The statistical analyais was conducted by means of PQStat ver. 1.4.4 software using ANOVA and Fisher tests. Results and conclusions : The obtained results show that the 94% of the surveyed people are familiar with the impact of HPV infection, but knowledge of accessory risk factors of cervical cancer is at low level. The study revealed that smoking is regarded as another risk factor by 13% of the surveyed people, HSV infection by 9%, multiple sex partners by 21%, and low hygiene level by 25%. Our examination revealed differences regarding the knowledge and available information sources by the respondents’ place of residence. Knowledge level of cervical cancer development depends on the place of residence and reaches the highest level in towns with over 20,000 inhabitants. The main source of information on cervical cancer risk factors is Internet and peer opinions.